TNFAIP3 Mediated by Novel Nano Composite Adsorbent on Tumor Necrosis Factor-α in Rats with Lumbar Disc Herniation by Inhibiting NF-κB Pathway: TNFAIP3 Mediated by Novel Nano Composite Adsorbent - Wang, Weishen; Ding, Hai (Cellular and Molecular Biology, 2022)
Mobile phones and computers have been widely used in the work of people. The incidence rate of lumbar disc herniation(LDH) has gradually increased and the trend toward younger age has been increasing. According to the epidemiological survey, about half of people will experience lumbar pain in their life and the resulting huge social and economic burden. It has important clinical significance for the treatment of lumbar disc herniation of TNFaIP3 mediated by a new nanocomposite adsorbent on tumor necrosis factor(TNF)- in rats with LDH by inhibiting the pathway. This paper mainly studies the mechanism and efficacy of TNFaIP3 mediated by a new nanocomposite adsorbent on TNF- in rats with LDH by inhibiting the pathway. Eight groups of human nucleus pulposus cells were randomly divided into four groups: high inhibition group, medium inhibition group, low inhibition group and no inhibition group. After interfering with human nucleus pulposus cells by inhibiting the pathway, the cells were allowed to stand for 24 hours to extract and detect TNF-, p-p65, P50, IKB and IKK in the signaling pathway to explore the mechanism of inhibiting pathway on TNF- in rats with LDH. The experimental results showed that after 24 hours of intervention, compared with the non-inhibition group, the expression of TNF in the low inhibition group, medium inhibition group and high inhibition group decreased relatively, and with the increase of inhibition degree, the expression of TNF in each group decreased more obviously, such as the expression of TNF in non-inhibition group was 1.48, the expression of TNF in low inhibition group was 1.31, the expression of TNF in medium inhibition group was 0.74, and the expression of TNF in high inhibition group was 0.58. The expression of P50 was 1.86 in non-inhibition, 1.47 in low inhibition, 1.32 in medium inhibition and 1.13 in high inhibition.